Back Pain Beliefs Are Related to the Impact of Low Back Pain in 17-Year-Olds - Smith, Anne; O'Sullivan, Peter; Beales, Darren; Straker, Leon (American Physical Therapy Association, 2012)
Background: Disability in adults with low back pain (LBP) is associated with negative back pain beliefs (BPBs). Adult BPBs can be positively influenced with education, resulting in reduced LBP disability. By late adolescence, the prevalence of LBP reaches adult levels. The relationship among LBP experience, LBP impact, and BPBs has not been investigated in late adolescence. Objective: The aim of this study was to document unknown relationships among LBP experience, LBP impact, and BPBs in 17-year-olds. Design: A cross-sectional study design was used. Methods: Adolescents (n=1,126) in the Raine Study provided full information on LBP, LBP impact (sought professional advice or treatment, taken medication, missed school or work, interfered with normal activities, interfered with physical activities), BPBs, and a number of covariates. Results: Back pain beliefs were more positive in participants with experience of LBP (X=30.2, SD=5.6) than in those without experience of LBP (X=28.5, SD=5.1). Individuals with LBP without activity modification impacts had more positive BPBs than those with activity modification impacts, even after adjustment for mental well-being and sex. The adjusted difference in BPBs between participants with experience of LBP but no activity modification impacts and those reporting all 3 activity modification impacts was 2.9 points (95% confidence interval=1.7 to 4.2). Participants with no activity modification impacts had more positive BPBs than those with no experience of LBP (adjusted difference=2.2 points, 95% confidence interval=1.4 to 2.9). More positive BPBs also were associated with female sex, lower body mass index, higher family income, better 36-Item Short-Form Health Survey (SF-36) Mental Health scale scores, and more positive primary caregiver beliefs.Limitations: Cause and effect cannot be ascertained with the cross-sectional design. Conclusion: Differences in BPBs are associated with different levels of LBP impact at 17 years of age. This finding provides a potential target for intervention early during the life course.